2017
DOI: 10.3945/ajcn.116.141804
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating freeze-dried strawberry powder into a high-fat meal does not alter postprandial vascular function or blood markers of cardiovascular disease risk: a randomized controlled trial

Abstract: Background: Postprandial dysmetabolism-an exaggerated spike in triglycerides, glucose, and insulin-increases cardiovascular disease risk by inducing oxidative stress, inflammation, and endothelial dysfunction. Polyphenol-rich foods may blunt these effects when they are incorporated into a high-fat, calorie-dense meal. Strawberries are a rich source of polyphenols, but there is little research on their postprandial effects. Objective: This study was designed to investigate the effect of adding 40 g freeze-dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
0
29
1
Order By: Relevance
“…Several studies have examined the effects of berries on lipid metabolism after chronic intake , but few have examined the effects of berries or fruit phenolic compounds on postprandial TG metabolism. Previous studies have shown reduced mean postprandial TG with berry intake over 6 hours in people who are overweight with hyperlipidemia and no effect in healthy indivduals or individuals with insulin resistance . In the current study we found postprandial TG was not different with raspberry intake compared with Control.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies have examined the effects of berries on lipid metabolism after chronic intake , but few have examined the effects of berries or fruit phenolic compounds on postprandial TG metabolism. Previous studies have shown reduced mean postprandial TG with berry intake over 6 hours in people who are overweight with hyperlipidemia and no effect in healthy indivduals or individuals with insulin resistance . In the current study we found postprandial TG was not different with raspberry intake compared with Control.…”
Section: Discussioncontrasting
confidence: 55%
“…Berries are rich in phytochemicals, and particularly phenolic compounds (2/3 flavonoids such as anthocyanins, catechins, quercetin, and kaempferol, and 1/3 phenolic acids such as ellagic acid), which are considered to be potent antioxidants inasmuch as they are able to scavenge ROS, chelate metal ions in vitro, and act synergistically between themselves and with micronutrients such as ascorbate and tocopherol [165,169,170]. The effects of berries on post-meal oxidative stress have been described in both the acute [171,172] and chronic settings [172]. In a chronic context, berries may exert anti-oxidative and anti-inflammatory effects by modulating mRNA expression in overweight and hypercholesterolemic individuals.…”
Section: Foods Nutrients and Other Dietary Substances That May Pmentioning
confidence: 99%
“…In the acute setting, the strawberry beverage (vs. the control) lowered postprandial increases in TG, HDL, and OxLDL at 3, 4, and 6 h after the meal. In the chronic setting, after a 6-week period, the strawberry beverage lowered mean cholesterol, LDL, TG, and OxLDL concentrations (when adjusted for fasting values) following the intake of a high-fat meal [172].…”
Section: Foods Nutrients and Other Dietary Substances That May Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included articles are summarized in Table 1 . Overall, 18 articles were included in the systematic review, of which 8 were conducted in the United States of America [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], 3 in Italy [ 24 , 25 , 26 ], 3 in the United Kingdom [ 12 , 27 , 28 ], and 2 in Chile [ 29 , 30 ]. One study each was conducted in Canada [ 31 ], and Austria [ 32 ].…”
Section: Resultsmentioning
confidence: 99%